2014
DOI: 10.1016/j.chiabu.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Parental spanking of 1-year-old children and subsequent child protective services involvement

Abstract: The majority of U.S. parents spank their children, often beginning when their children are very young. We examined families (N=2,788) who participated in a longitudinal community-based study of new births in urban areas. Prospective analyses examined whether spanking by the child's mother, father, or mother's current partner when the child was 1-year-old was associated with household CPS involvement between age 1 and age 5. Results indicated that 30% of 1-year-olds were spanked at least once in the past month.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 50 publications
2
46
0
2
Order By: Relevance
“…Unfortunately, because no existing national, longitudinal survey includes both income data and administrative data on CPS involvement, self-reports are commonly used in population-based studies (Berger et al, 2009; Lee et al, 2014; Nam et al, 2006; Slack et al, 2011). Prior research documents consistency in the predictors of both self-reported and administratively documented CPS involvement, as well as in the magnitudes of association between these predictors and each measure (Slack et al, 2011).…”
Section: Data and Measuresmentioning
confidence: 99%
“…Unfortunately, because no existing national, longitudinal survey includes both income data and administrative data on CPS involvement, self-reports are commonly used in population-based studies (Berger et al, 2009; Lee et al, 2014; Nam et al, 2006; Slack et al, 2011). Prior research documents consistency in the predictors of both self-reported and administratively documented CPS involvement, as well as in the magnitudes of association between these predictors and each measure (Slack et al, 2011).…”
Section: Data and Measuresmentioning
confidence: 99%
“…Parents who routinely employ spanking are three times as likely to be substantiated for maltreatment (Durrant et al 2009). Similarly, early parental spanking of infants by age one predicts future child protective services involvement (Lee et al 2014). Given the context within which physical abuse thus arises, many view abuse as occurring on a parent–child aggression (PCA) continuum (Gershoff 2010; Graziano 1994; Greenwald et al 1997; Rodriguez, 2010a; Straus 2001; Whipple and Richey 1997), wherein physical discipline at one endpoint progressively intensifies to become physical abuse at the other endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggest that a substantial proportion of medical staff do not view spanking as harmful to children and are either unaware of or discount research findings regarding the potential harms to children that have been linked with spanking (Gershoff & Grogan-Kaylo, 2016; Lee et al, 2014; MacKenzie, Nicklas, Waldfogel, & Brooks-Gunn, 2012; Zolotor et al, 2008). Thus, a first strategy would be to educate staff by summarizing and disseminating the large body of research findings that link spanking to increased risks of physical and emotional harm to children (e.g., Gershoff & Grogan-Kaylor, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…One large study in North Carolina found that parents who spanked were almost three times as likely to engage in abusive behaviors, such as kicking, beating, and hitting with objects, than were parents who did not spank (Zolotor, Theodore, Chang, Berkoff, & Runyan, 2008). In another study, parents who spanked their 1 year olds were 36% more likely to have involvement with child protective services before their children turned 5 than were parents who did not spank (Lee, Grogan-Kaylor, & Berger, 2014). Reviews of maltreatment records in Canada have revealed that 75% of substantiated cases of physical abuse start out as spanking (Durrant, Trocmé, Fallon, Milne, Black, & Knoke, 2006).…”
Section: Introductionmentioning
confidence: 99%